Respon Pertumbuhan dan Toleransi Kalus Talinum paniculatum terhadap Cekaman Logam Berat Krom (Cr) - Ratih Restiani; Kaban, Sarah M.P.; Sekar, Astrid A.; Matheos, Josiah H. (Jurnal Biologi Papua, 2024)
The escalating chromium (Cr) heavy metal contamination necessitates effective remediation strategies like phytoremediation. Selecting chromium-tolerant plant species is crucial for successful phytoremediation, achievable through in vitro culture to induce somaclonal variations with resistance traits. Talinum paniculatum, an ornamental plant with robust roots and stress resilience, is a promising candidate for chromium tolerance studies. This research assesses T. paniculatum callus response to chromium stress, focusing on growth and tolerance indices. Results demonstrate the callus's resilience to increasing Cr concentrations, reflected in biomass increase (0.117–0.150 g) and a high tolerance index (TI) of 77.78–100%. Structural integrity and color remained stable throughout the study period, underscoring T. paniculatum's potential for chromium phytoremediation.